Pengabdian kepada Masyarakat melalui Optimalisasi Detail Engineering Design (DED) Struktur Masjid Berbasis Standar Konstruksi Nasional - Nur Fithriani Fatma Cholida; Thalita Zhafira; Iryan Dwi Handayani; Trias Widorini (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
The mosque is the center of religious and social activities of the community. Its construction requires careful technical planning. This will ensure that the building is safe, efficient, and in accordance with Standar Nasional Indonesia (SNI). The purpose of this community service activity is to provide technical assistance during the process of preparing the Detail Engineering Design (DED) of the Assafi Qolbu Mosque building located in Mranggen District, Demak Regency. Using an expert-driven design approach, the assistance was carried out by a team of Civil Engineering lecturers at Semarang University. Site surveys, needs analysis, technical working drawings, and selection of structural materials according to standards were all work carried out. The activity resulted in a one-story building structure technical document (DED) that included the planning of strip and footplate foundations, sloofs, columns, beams, floor slabs, and light reinforced roof structures. A well-designed DED ensures that the durability of the building is guaranteed to meet the aspects of structural safety and material efficiency. This activity not only creates design documents, but also increases partners' understanding of the importance of involving experts in the construction of mosques, especially their structures. It is expected that this assistance will serve as an implementative model for the construction of worship facilities based on Indonesian National Standards.